Aerodynamic thermal environment-resistant low-absorption high-emission thermal control coating and preparation method thereof
By designing multi-layer structural coatings, combined with specific fillers and processes, the problem that existing thermal control coatings cannot meet the requirements of water resistance, pneumatic heat resistance and thermal control performance, and the spacecraft thermal balance and stability in complex environments are achieved , has low absorption and high emission, heat insulation, waterproofing and heat resistance.
Patent Information
- Application Number
- CN202411627737.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-17
AI Technical Summary
The existing thermal control coatings cannot meet the requirements of water, aerodynamic heat resistance and thermal control performance at the same time, cannot maintain the thermal balance of the spacecraft in complex environments, and cannot adapt to the various environmental needs of the spacecraft during the spacecraft's orbit.
Using functional group modified phenylmethyl silicone resin as a binder, combined with fillers such as boron nitride, alumina, hollow glass microspheres and zinc titanate powder, a multi-layer structural coating was designed, and through specific preparation and The spraying process forms a coating with low absorption and high emission performance.
The stability and thermal control performance of the coating in high temperature, high speed pneumatic erosion and complex environments are achieved, and good heat insulation, waterproofing and heat resistance are provided to ensure the long-term stability of the spacecraft during orbit.
Smart Images

Figure CN119320601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface engineering, in particular to a low-absorption and high-emission thermal control coating resistant to aerodynamic thermal environment and a preparation method thereof. Background Art
[0002] Thermal control coating is an important component of the thermal control system of spacecraft, and plays an important role in achieving thermal balance of spacecraft in the high vacuum space environment. Low-absorption and high-emission thermal control coating has the function of reducing solar radiation absorption and increasing infrared radiation heat dissipation. It can play a certain role in heat dissipation for the complex temperature environment experienced by spacecraft under solar radiation at different positions during on-orbit operation, and prevent the temperature in the cabin from being too high and exceeding the operating temperature of the load and electronic components.
[0003] As the size of spacecraft continues to increase, the environment that spacecraft experience throughout their life cycle is no longer a single space vacuum radiation environment. Instead, they are directly facing multiple complex environments such as outdoor rain and humid environments and high-temperature, high-speed atmospheric heat flow erosion. They still need to ensure stable performance during in-orbit operations in space.
[0004] The preparation method in the prior art uses ceramic precursor resin as a film-forming material, adds hollow glass microspheres and lightweight nanomaterials as low thermal conductivity fillers, and the thermal conductivity of the coating reaches 0.05-0.1W / m·k, and the temperature resistance of the coating reaches 1200°C. However, since it does not have the thermal radiation performance of low absorption and high emission, the thermal control coating prepared by this preparation method cannot meet the application environment requirements of subsequent spacecraft.
[0005] The thermal control coatings in the prior art cannot simultaneously meet the above-mentioned performance requirements such as water resistance, aerodynamic heat resistance, and thermal control. In order to improve the operational stability of the spacecraft cabin after experiencing various environments, a method for preparing a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments is invented, which has important research significance and application background. Summary of the invention
[0006] The present invention provides a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments and a preparation method thereof. The coating is designed to improve the operational stability of a spacecraft cabin after experiencing a variety of environments, thereby meeting the on-orbit space application environment requirements of subsequent spacecraft, such as maintaining the thermal equilibrium state required for the spacecraft in complex environments such as rain, high-temperature and high-speed aerodynamic scouring, high and low temperature alternation, and space radiation.
[0007] In the first aspect, a low-absorption and high-emission thermal control structure resistant to aerodynamic thermal environment is provided, comprising a substrate and a coating; the coating is a bottom layer structure, with functional group-modified phenyl methyl silicone resin components AB as a binder, resin component A comprising a base resin and a cross-linking catalyst, and resin component B comprising a base resin and a cross-linking agent; the bottom layer structure comprises a bottom layer and a surface layer; the bottom layer comprises a mixed powder of boron nitride, alumina and hollow glass microspheres as a filler; the surface layer comprises zinc titanate powder and alumina whiskers as fillers.
[0008] In combination with the first aspect, in certain implementations of the first aspect, the mass fractions in the bottom layer meet the following requirements: 58 to 69 parts of resin A component, 100 parts of resin B component, 222.7 to 334 parts of boron nitride, and 111.3 to 167 parts of aluminum oxide;
[0009] The mass proportions in the surface layer meet the following requirements: 58-69 parts of resin A component, 100 parts of resin B component, and 501-668 parts of total filler, wherein the proportion of zinc titanate powder to filler is greater than or equal to 80%, and the proportion of aluminum oxide whisker to filler is less than or equal to 20%.
[0010] In combination with the first aspect, in certain implementations of the first aspect, the base resin of the resin component A and / or the resin component B includes at least one of a vinyl-terminated methylphenyl silicone resin, a hydroxyl-terminated methylphenyl silicone resin, and an alkoxy-terminated methylphenyl silicone resin.
[0011] In conjunction with the first aspect, in some implementations of the first aspect, the structure satisfies at least one of the following:
[0012] The boron nitride is hexagonal boron nitride in the form of flakes with a particle size of 10 to 50 microns, or the boron nitride is hexagonal boron nitride whiskers with a diameter of 0.5 to 1 micron and a length of 10 to 30 microns;
[0013] The aluminum oxide is an aluminum oxide whisker with an aspect ratio of 10 to 20, a diameter of 0.5 to 1 micron, and a length of 10 microns;
[0014] The cross-linking catalyst comprises at least one of the following: dibutyltin dilaurate, tetramethylammonium hydroxide, butyl titanate;
[0015] The crosslinking agent includes at least one of the following: tetraethyl orthosilicate, diethylenetriamine, KH-CL silicon nitrogen crosslinking agent;
[0016] The hollow glass microspheres have a particle size of 15 to 45 microns and a wall thickness of 2 microns;
[0017] The thickness of the bottom layer is 300-600 μm, and the thickness of the surface layer is 50-100 μm;
[0018] A first primer layer is provided between the substrate and the bottom layer, and a second primer layer is provided between the bottom layer and the surface layer. The first primer layer and the second primer layer are both obtained by spraying a primer, and the primer comprises a resin A component and a resin B component. The mass fractions of the primer satisfy 58 to 69 parts of the resin A component and 100 parts of the resin B component.
[0019] The substrate includes one of a low-density thermal ablation resistant material, an aluminum alloy, a magnesium alloy, stainless steel, and a titanium alloy.
[0020] In a second aspect, a method for preparing a low-absorption and high-emission thermal control coating resistant to aerodynamic thermal environments is provided. The method is applied to a low-absorption and high-emission thermal control structure resistant to aerodynamic thermal environments as described in any one of the implementations of the first aspect above to prepare a coating on a substrate. The method comprises:
[0021] (1) Preparation of base coating: n-heptane solvent is added to resin component A, mixed and stirred to perform preliminary dispersion. After resin component A and solvent are evenly dispersed, resin component B is added and stirred continuously. After dispersion, filler powder is added and sand-milled with glass beads to evenly disperse the filler. After filtering, paint A is formed. n-heptane is added to hollow glass microspheres to evenly wet the hollow glass microspheres to form solution B, which is mixed and stirred with paint A to obtain an evenly dispersed base coating.
[0022] (2) Preparation of surface coating: Add a mixed solvent of n-heptane and xylene to the resin component A, mix and stir to perform preliminary dispersion. After the resin component A and the solvent are evenly dispersed, add the resin component B, continue stirring, add zinc titanate powder, aluminum oxide whiskers and glass beads, and disperse by sand grinding to make the filler evenly dispersed;
[0023] (3) Coating preparation: The coating is prepared by air spraying. First, spray the primer on the surface of the substrate. After the paint is evenly stirred, spray the paint. First, spray the base coat. After the base coat is cured, spray the primer and top coat, and then bake and cure.
[0024] In conjunction with the second aspect, in certain implementations of the second aspect, step (1) satisfies at least one of the following:
[0025] Resin component A is a mixture of base resin, diluent and cross-linking catalyst, and the solid content of resin component A is 58-69%;
[0026] The resin B component is a mixture of a base resin and a crosslinking agent, and the solid content of the resin B component is 100%;
[0027] The amount of cross-linking catalyst added is 1 to 3% of the resin component A and the resin component B;
[0028] The amount of crosslinking agent added is 4-6% of the resin component A and the resin component B;
[0029] The diluent is at least one of the following: xylene, heptane, cyclohexane, n-hexane, butyl acetate;
[0030] In paint A, the resin A component is 100 parts, the resin B component is 100 parts; the filler boron nitride is 222.7-334 parts, the filler aluminum oxide whisker powder is 111.3-167 parts, the solvent is 501-1002 parts, and the glass beads are 334-501 parts;
[0031] In solution B, the amount of hollow glass microspheres added is 35-50% of the volume of paint A, and the amount of n-heptane added is 35-50% of the volume of paint A;
[0032] The glass beads used in the sand grinding process of paint A have a size of 2 to 3 mm, the speed of the disperser during the sand grinding process is 1000 to 1300 r / min, and the dispersion time is 2 to 4 h;
[0033] The solution B was stirred by a stirrer at a speed of 400 to 500 r / min for 2 to 3 hours.
[0034] In conjunction with the second aspect, in certain implementations of the second aspect, step (2) satisfies at least one of the following:
[0035] The resin A component is 100 parts, the solid content of the resin A component is 58-69 parts, the resin B component is 100 parts; the total amount of filler consisting of a mixture of zinc titanate powder and aluminum oxide whiskers is 501-668 parts, the proportion of zinc titanate powder in the filler is greater than or equal to 80%, the proportion of aluminum oxide whiskers in the filler is less than or equal to 20%, the total amount after adding a mixed solvent of n-heptane and xylene is 668-960.25 parts, and the glass beads are 668-835 parts;
[0036] The mass ratio of xylene:n-heptane is 1:1 to 1:2;
[0037] The size of glass beads is 2 to 3 mm;
[0038] During the sand grinding process, the speed of the disperser is 1000-1500 r / min, and the dispersion time is 2-4 hours.
[0039] In conjunction with the second aspect, in certain implementations of the second aspect, step (3) satisfies at least one of the following:
[0040] The primer is a mixture of resin component A and resin component B, wherein the resin component A is 100 parts, the solid content of the resin component A is 58-69 parts, the resin component B is 100 parts, and n-heptane is 400-600 parts;
[0041] The test piece substrate is any of the following: low-density thermal ablation resistant material, aluminum alloy, magnesium alloy, stainless steel, titanium alloy;
[0042] The bottom layer spraying thickness is 300-600μm, and the curing method used is high temperature curing at 50-100℃ for 12-24h;
[0043] The surface spray thickness is 50-100 μm, and the curing method used is high-temperature curing at 60-100°C for 24 hours.
[0044] In combination with the second aspect, in certain implementations of the second aspect, the bottom layer spray curing system is to cure at 50° C. for 4 hours and then raise the temperature to 80° C. for 20 hours.
[0045] In combination with the second aspect, in certain implementations of the second aspect, the surface layer spray curing system is a curing temperature of 80° C. for 24 hours.
[0046] Compared with the prior art, the solution provided by the present invention includes at least the following beneficial technical effects:
[0047] (1) The present invention provides a method for preparing a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments, which has the following characteristics: a) White appearance, uniform surface, no blistering, no cracks, and no shedding. b) Thickness: 350-700 μm (the thickness of the bottom layer is 300-600 μm, and the thickness of the surface layer is 50-100 μm). c) Solar absorption ratio: 0.18±0.02; d) Hemispherical emissivity: 0.86±0.02. e) Thermal cycle performance: After 100 times of normal pressure thermal cycle tests at -196℃ to 150℃, the coating has a uniform appearance color and no obvious color difference. The coating does not fall off, and the thermal radiation performance (solar absorption ratio and hemispherical emissivity) does not change. f) Aerodynamic thermal resistance: The low-absorption and high-emission thermal control coating recovers enthalpy of 716 KJ / kg and cold wall heat flux of 24 KW / m after 180-240s of airflow. 2 Shear force 44Pa time not less than 40s, air flow recovery enthalpy 1120KJ / kg cold wall heat flux 50KW / m 2 Shear force 50Pa time not less than 60s, air flow recovery enthalpy 882KJ / kg cold wall heat flux 25KW / m 2 The coating has no appearance change after high-temperature and high-speed pneumatic scouring with a shear force of 56Pa for not less than 70s. The low-absorption and high-emission thermal control coating can stably exist in an aerobic environment of 480℃ for 180s. g) Thermal insulation performance: The thermal conductivity of the coating is in the range of 0.08 to 0.15W / m·k at room temperature. h) Waterproof performance: The water absorption rate of the coating is less than 0.5% after being soaked in water for 24 hours; i) The coating adhesion is tested by the pull-belt method and the coating does not fall off.
[0048] (2) Compared with the prior art, the present invention relates to a method for preparing a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments. Hexagonal boron nitride with high heat capacity is used as the main filler, so that the coating absorbs heat in a high-temperature environment but heats up slowly. At the same time, due to the high thermal conductivity of hexagonal boron nitride in the horizontal direction, a large amount of heat can be prevented from accumulating in one place for a long time in a high-temperature environment, causing the silicone resin to decompose; aluminum oxide whiskers are added to enhance the mechanical strength inside the coating, reduce the thermal expansion coefficient of the coating, form a coating structure, and interface overlap structure design, and obtain a heat-resistant, waterproof, stable, low-absorption, high-emission multifunctional thermal control coating. The coating preparation operation process is simple and convenient for construction, and the coating has a certain toughness. It can be applied to complex structures and adapt to a variety of rigid, flexible and other substrate types. It is particularly suitable for the surface of porous and low-density heat-proof materials, and plays a role in completing the effective sealing of low-density porous heat-proof materials, controlling the interface bonding force, and ensuring multiple waterproof application performances. While meeting the requirements of high temperature resistance, heat insulation, waterproofness and moisture resistance of the coating, it also guarantees the thermal control requirements of the surface application and the long-term space environment stability requirements.
[0049] In addition to the thermal control function of traditional thermal control coatings or coating materials on the surface of in-orbit spacecraft, this new thermal control coating also has the function of protecting the spacecraft cabin from complex humid and hot environments, salt fog, rain, and other environments on the ground, and from high-temperature and high-speed airflow environments. That is, under this preparation method, the thermal control coating extends its function from only playing a role in the space segment to playing a role in the ground environment and the atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The bottom and surface structures of a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments are schematically shown;
[0051] Figure 2 The following are appearance diagrams of a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments, wherein (a) is an appearance diagram of the coating on a thermal protection material; (b) is an appearance diagram of the coating after normal pressure thermal cycling;
[0052] Figure 3 This is the appearance of a low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environment after being subjected to an aerodynamic thermal scour test;
[0053] Figure 4 The appearance of the coatings in Comparative Examples 1, 2, 3, 4, 5, 6, and 7 after being subjected to the air heat erosion test;
[0054] Figure 5 Schematic diagram of the appearance of the low-absorption and high-emission thermal control coating for resisting aerodynamic thermal environment of the present invention after being implemented for large-sized thermal ablation-resistant materials. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0056] like Figure 1 As shown, the present invention provides a low-absorption and high-emission thermal control structure resistant to aerodynamic thermal environment, including a substrate and a coating, and the coating is attached to the substrate. The coating is a bottom layer structure, with functional group-modified phenyl methyl silicone resin AB components as a binder, resin A component includes a base resin and a cross-linking catalyst (excluding a diluent), and resin B component includes a base resin and a cross-linking agent; the bottom layer structure includes a bottom layer and a surface layer; the bottom layer uses a mixed powder of boron nitride, aluminum oxide, and hollow glass microspheres as fillers; the surface layer uses zinc titanate powder and aluminum oxide whiskers as fillers.
[0057] The surface layer enhances the thermal radiation of the spacecraft in space and ensures its stability in the space environment. It plays a role in dissipating the temperature inside the spacecraft and has a certain heat resistance. The bottom layer is a high-temperature resistant thermal insulation coating, which provides a certain thermal insulation performance and bonding strength between the coating and the substrate (low-density thermal protection material) to prevent the thermal protection layer of the spacecraft from being decomposed by heat in the aerodynamic thermal environment of the rocket's ascent. It also has a certain thermal conductivity to prevent the external heat from accumulating on the surface layer, causing the surface layer to be decomposed by heat and destroying the thermal control performance of the coating. At the same time, the coating preparation process is simple, can be cured at low temperature, and has a wide range of application scenarios.
[0058] In some embodiments, the weight proportions in the bottom layer are as follows: 58 to 69 parts of resin A component, 100 parts of resin B component, 222.7 to 334 parts of boron nitride, and 111.3 to 167 parts of aluminum oxide.
[0059] In some embodiments, the mass ratio of boron nitride to aluminum oxide is 2:1 to 3:1.
[0060] In some embodiments, the mass proportions in the surface layer are as follows: 58-69 parts of resin A component, 100 parts of resin B component, and 501-668 parts of total filler, of which zinc titanate powder accounts for 75%-80% and aluminum oxide accounts for 20%-25%.
[0061] In some embodiments, the base resin of the resin A component and / or the resin B component includes at least one of a hydroxyl-terminated methylphenyl silicone resin, a vinyl-terminated methylphenyl silicone resin, and an alkoxy-terminated methylphenyl silicone resin.
[0062] In some embodiments, the boron nitride is preferably hexagonal boron nitride, in a flake shape with a particle size of 10 to 50 microns.
[0063] In some embodiments, the boron nitride is preferably hexagonal boron nitride whiskers with a diameter of 0.5 to 1 micron and a length of 10 to 30 microns.
[0064] In some embodiments, the aluminum oxide is preferably aluminum oxide whiskers with an aspect ratio of 10 to 20, a diameter of 0.5 to 1 micrometer, and a length of 10 micrometers.
[0065] In some embodiments, the cross-linking catalyst includes at least one of the following: dibutyltin dilaurate, tetramethylammonium hydroxide, butyl titanate.
[0066] In some embodiments, the crosslinking agent includes at least one of the following: tetraethyl orthosilicate, diethylenetriamine, and KH-CL silicon nitrogen crosslinking agent.
[0067] In some embodiments, the hollow glass microspheres have a particle size of 15 to 45 microns and a wall thickness of 2 microns.
[0068] In some embodiments, the thickness of the bottom layer is 300-600 μm, and the thickness of the surface layer is 50-100 μm.
[0069] In some embodiments, a first primer layer is disposed between the substrate and the bottom layer, and a second primer layer is disposed between the bottom layer and the surface layer. Both the first primer layer and the second primer layer are obtained by spraying a primer, and the primer includes a resin A component and a resin B component. The mass fractions of the primer satisfy 58 to 69 parts of the resin A component and 100 parts of the resin B component.
[0070] In some embodiments, the substrate includes but is not limited to low-density heat-resistant ablation material, aluminum alloy, magnesium alloy, stainless steel, titanium alloy, etc. Preferably, a low-density heat-resistant material is used.
[0071] The present invention also provides a method for preparing a low-absorption and high-emission thermal control coating resistant to aerodynamic thermal environment, wherein the main raw materials of the structure include: zinc titanate powder, hollow glass microspheres, boron nitride, and aluminum oxide whiskers as fillers, silicone resin as a binder, and n-heptane and xylene as solvents. The specific steps are as follows.
[0072] (1) Preparation of base coating: n-heptane solvent is added to resin component A, mixed and stirred for preliminary dispersion. After resin component A and solvent are evenly dispersed, resin component B is added and stirred continuously. After dispersion, filler powder is added and sand-milled with glass beads to evenly disperse the filler. After filtering, paint A is formed. n-heptane is added to hollow glass microspheres to evenly wet the hollow glass microspheres to form solution B, which is mixed and stirred with paint A to obtain an evenly dispersed base coating.
[0073] (2) Preparation of surface coating: Add a mixed solvent of n-heptane and xylene to the resin component A, mix and stir to perform preliminary dispersion. After the resin component A and the solvent are evenly dispersed, add the resin component B and continue stirring. Add zinc titanate powder, alumina whiskers and glass beads, and disperse by sand grinding to ensure that the filler is evenly dispersed.
[0074] (3) Coating preparation: The coating is prepared by air spraying. First, the primer is sprayed on the surface of the substrate. After the coating is evenly stirred, the coating is sprayed. The base coating is sprayed first. After the base coating is cured, the primer and the top coating are sprayed. After baking and curing for 12 to 24 hours, a low-absorption and high-emission thermal control coating with resistance to aerodynamic thermal environment is obtained.
[0075] (4) A low-absorption and high-emission thermal control coating that is resistant to aerodynamic thermal environments. Application objects include: the outer surface of spacecraft that needs to be resistant to aerodynamic thermal environments, waterproof, and moisture-proof.
[0076] In step (1), the filler powder is one or more mixed filler powders such as aluminum oxide whisker powder, boron nitride, boron nitride whisker, etc., the boron nitride is preferably hexagonal boron nitride, flaky, and has a particle size of 10 to 50 microns, the aluminum oxide whisker is preferably aspect ratio 10 to 20, diameter 0.5 to 1 micron, length 10 microns, and the boron nitride whisker is preferably hexagonal boron nitride, diameter 0.5 to 1 micron, length 10 to 30 microns; the silicone resin is one or a mixture thereof, the resin is A resin B component, the resin A component is a base resin, a small amount of diluent and a crosslinking catalyst mixture, and the resin B component is a base resin and a crosslinking agent mixture; the resin A component solid content is 58 to 69% (67%), and the resin B component solid content is 100%; the crosslinking catalyst addition amount is 1 to 3% of the resin A component and the resin B component, and the crosslinking agent addition amount is 4 to 6% of the resin A component and the resin B component. For example, in 20g component A + 20g component B, there are 40×0.01~40×0.03=0.4~1.2g of catalyst, and 40×0.04~40×0.06=1.6~2.4g of crosslinking agent. When the catalyst addition amount is 2%, component A = 12.6g of base resin + 0.8g of catalyst + 6.6g of diluent, and when the crosslinking agent addition amount is 5%, component B = 19g of base resin + 1g of crosslinking agent. The filler solvent is analytical pure n-heptane, the particle size of hollow glass microbeads is 15~45 microns, and the wall thickness is 2 microns. The diluent is xylene, heptane, cyclohexane, n-hexane, butyl acetate, etc. The catalyst is dibutyltin dilaurate, tetramethylammonium hydroxide, butyl titanate, etc. The crosslinking agent is tetraethyl orthosilicate, diethylenetriamine, KH-CL silicon nitrogen crosslinking agent, etc.
[0077] In step (1), 100 parts of resin A component (solid content 67 parts); 100 parts of resin B component; 222.7-334 parts of boron nitride filler, 111.3-167 parts of aluminum oxide whisker powder filler, (pigment-to-base ratio 2:1-3:1) 501-1002 parts of solvent (the solvent is 1-1.5 times the total amount of resin A+B and filler), 334-501 parts of glass beads (1:1 with filler), the above is paint A. After the paint A is sanded and dispersed, solution B is slowly added, and after stirring and dispersing again, a uniform base coating is formed. Solution B is composed of n-heptane and hollow glass microspheres, and the amount of hollow glass microspheres added in solution B is 35-50% of the volume of paint A, and the amount of n-heptane added is 35-50% of the volume of paint A.
[0078] In step (1), the glass beads used in the sand grinding process of paint A have a size of 2 to 3 mm, the speed of the disperser during the sand grinding process is 1000 to 1300 r / min, and the dispersion time is 2 to 4 hours. The second stirring process uses a stirrer to disperse and stir at a speed of 400 to 500 r / min. After stirring for 2 to 3 hours, a base coating is obtained.
[0079] In step (2), the surface coating comprises 100 parts of resin A component (solid content 67%) and 100 parts of resin B component; a mixture of zinc titanate powder and aluminum oxide whisker is used as filler, the zinc titanate powder accounts for greater than or equal to 80% of the filler, and the aluminum oxide whisker accounts for less than or equal to 20% of the filler, with a total amount of 501 to 668 parts (3:1 to 4:1); a total amount of 668 to 960.25 parts of mixed solvent (1 to 1.15 times the total amount of resin A+B and filler, xylene:n-heptane 1:1 to 1:2), and 668 to 835 parts of glass beads (1 times the total amount of resin A+B and filler), which are dispersed by sand grinding to form a uniform surface coating.
[0080] In step (2), the organic silicone resin is one of hydroxyl-terminated methylphenyl silicone resin, alkoxy-terminated methylphenyl silicone resin or a mixture thereof, the solid content of resin A component is 58-69% (67%); the solid content of resin B component is 100%; the zinc titanate filler is a homemade powder, and the preparation method refers to patent CN107827151A "A preparation method and application of zinc titanate powder"; the solvent is a mixture of n-heptane and xylene, 50%-67% n-heptane and 33%-50% xylene; the size of the glass beads is 2-3 mm.
[0081] In step (2), the speed of the disperser during the sand milling process is 1000 to 1500 r / min, and the dispersion time is 2 to 4 hours.
[0082] In step (3), the primer is a mixture of resin component A and resin component B, wherein the resin component A is 100 parts (solid content 67%), the resin component B is 100 parts, and n-heptane is 400-600 parts, which are stirred and dispersed to form the primer. The test piece substrate includes but is not limited to low-density thermal ablation resistant materials, aluminum alloys, magnesium alloys, stainless steel, titanium alloys, etc. Preferably, low-density thermal resistant materials are used.
[0083] In step (3), the bottom layer is sprayed with a thickness of 300 to 600 μm, and the curing method used is 50 to 100°C high temperature curing for 12 to 24 hours, preferably, the temperature is 50°C for curing for 4 hours and then raised to 80°C for curing for 20 hours. The surface layer is sprayed with a thickness of 50 to 100 μm, and the curing method used is 60 to 100°C high temperature curing for 24 hours, preferably, the temperature is 80°C for curing for 24 hours.
[0084] The combination of steps (1), (2), and (3) ensures that when the coating is subjected to external high-temperature, high-speed airflow, the heat will not remain on the surface layer for a long time after accumulation, but a certain amount will be transferred to the bottom layer. The coating also has a certain heat insulation capacity, which can prevent the low-density heat-resistant material of the coating substrate from being heated, burned and decomposed in a high-speed air heat environment within 180 to 240 seconds.
[0085] Example 1
[0086] The steps of coating preparation include:
[0087] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 100.2g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 44.54g of boron nitride powder, 22.26g of aluminum oxide whiskers, and 67g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 35% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0088] (2) Preparation of surface coating: Add 20 g of hydroxyl-terminated methylphenyl silicone resin component A and 120 g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20 g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 80.16 g of zinc titanate powder, 20.04 g of aluminum oxide whiskers, 33.64 g of mixed solvent, and 133.6 g of glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000 r / min for 2 hours. The resulting paint is evenly dispersed without precipitation.
[0089] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0090] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 400-550 μm; c) solar absorption ratio: 0.20; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, and the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high-temperature and high-speed pneumatic flushing, the appearance of the coating does not change; g) thermal insulation performance: the thermal conductivity of the coating is 0.125 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.3% after being immersed in water for 24 hours; i) the coating adhesion is tested by the pull-belt method without shedding.
[0091] Example 2
[0092] The steps of coating preparation include:
[0093] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 133.6g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 66.8g of boron nitride powder, 33.4g of aluminum oxide whiskers, and 101g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 35% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0094] (2) Preparation of surface coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 120g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 133.6g of zinc titanate powder, 72.05g of mixed solvent and 167g of glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000r / min for 2h. The resulting paint is evenly dispersed without precipitation.
[0095] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0096] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 400-550 μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, and the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high-temperature and high-speed pneumatic flushing, the appearance of the coating does not change; g) thermal insulation performance: the thermal conductivity of the coating is 0.12 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.3% after being immersed in water for 24 hours; i) the coating adhesion is tested by the pull-belt method without shedding.
[0097] Comparative Example 1
[0098] The difference between this example and Example 2 is that the filler of the base coating is different. Boron nitride is replaced with mica powder. After preparation, the coating obtained bubbles and cracks under high temperature environment.
[0099] The steps of coating preparation include:
[0100] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 133.6g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 66.8g of mica powder, 33.4g of aluminum oxide whisker powder, and 101g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 35% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0101] (2) Preparation of surface coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 120g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 133.6g of zinc titanate powder, 72.05g of mixed solvent and 167g of glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000r / min for 2h. The resulting paint is evenly dispersed without precipitation.
[0102] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0103] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 400-550 μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high temperature and high-speed pneumatic scouring, the coating surface has blistering and cracking; g) thermal insulation performance: the thermal conductivity of the coating is 0.12 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.3% after being immersed in water for 24 hours; i) the coating adhesion is tested by the pull-belt method and there is shedding.
[0104] In this comparative example, boron nitride is replaced by mica powder. Since mica powder has a lower specific heat capacity than boron nitride, the specific heat capacity of the bottom layer of the coating is also correspondingly lower. After applying an external heat source, the heat is transferred to the bottom layer and the temperature of the bottom layer rises rapidly. At the same time, the heat diffuses to the surface layer, causing the coating to decompose, release gas and bubble due to heat.
[0105] Comparative Example 2
[0106] The difference between this example and Example 2 is that the amount of aluminum oxide whiskers added to the bottom layer is less than the required range, and after preparation, a coating is obtained.
[0107] The steps of coating preparation include:
[0108] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 133.6g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 33.4g of aluminum oxide whisker powder, 66.8g of boron nitride, and 101g of glass beads. Use a high-speed dispersing device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 60% of the volume of A hollow glass microbeads to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0109] (2) Preparation of surface coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 120g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 133.6g of zinc titanate powder, 72.05g of mixed solvent and 167g of glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000r / min for 2h. The resulting paint is evenly dispersed without precipitation.
[0110] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0111] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 500-650μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196℃~150℃, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180s of high temperature and high-speed pneumatic scouring, the coating cracks and the surface layer bonding strength decreases; g) thermal insulation performance: the thermal conductivity of the coating is 0.12W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.4% after being soaked in water for 24h; i) the coating bonding strength is detached by the pulling tape method.
[0112] The amount of aluminum oxide whiskers added to the bottom layer is small, and the reinforcement effect of the coating system is not achieved. The overall thermal expansion coefficient of the coating is high, and the elasticity decreases after heating. After being in a high temperature environment, the thermal expansion coefficient does not match that of the substrate, cracking occurs, and it causes falling off.
[0113] Comparative Example 3
[0114] The difference between this example and Example 2 is that the amount of hollow glass microsphere filler added in the bottom layer is lower, and a coating is obtained after preparation.
[0115] The steps of coating preparation include:
[0116] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 133.6g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 66.8g of boron nitride powder, 33.4g of aluminum oxide whiskers, and 101g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 20% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0117] (2) Preparation of surface coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 120g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 133.6g of zinc titanate powder, 72.05g of mixed solvent and 167g of glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000r / min for 2h. The resulting paint is evenly dispersed without precipitation.
[0118] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0119] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 350-400 μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high temperature and high-speed pneumatic scouring, the coating cracks; g) thermal insulation performance: the thermal conductivity of the coating is 0.171 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.4% after being exposed to rain for 24 hours; i) the coating adhesion is tested by the pull-belt method for coating shedding.
[0120] The amount of hollow glass microspheres added to the bottom layer is reduced, and the thermal conductivity of the coating is increased, which reduces the thermal insulation performance of the bottom layer and the overall coating. After the coating is heated by an external heat source, a large amount of heat is quickly transferred to the heat-resistant material substrate. After continuous accumulation, the heat-resistant material eventually reaches the decomposition temperature and decomposes and carbonizes, which reduces the bonding stability between the coating and the substrate interface. After experiencing a high temperature environment, the coating will expand and shrink to a certain extent. Therefore, the reduced bonding force between the coating and the substrate interface will cause the coating to crack after being heated. The bottom layer needs to have a certain thermal insulation capacity to keep the temperature of the heat-resistant material lower than its decomposition temperature to ensure the stability of the coating.
[0121] Comparative Example 4
[0122] The difference between this example and Example 2 is that there is no surface layer, and after preparation, a coating is obtained.
[0123] The steps of coating preparation include:
[0124] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 133.6g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 66.8g of boron nitride powder, 33.4g of boron nitride, and 101g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 35% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0125] (2) Coating preparation: First, spray the primer on the surface of the low-density heat-resistant material. The primer is sprayed 2 to 3 times, and the base layer is sprayed after the surface is dry; the base layer is sprayed 4 to 5 times, dried in the shade for 8 to 16 hours, and then cured at 50°C for 4 hours, and then heated to 80°C for 20 hours to obtain the coating.
[0126] The coating prepared in this example a) has an off-white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 300-400 μm; c) solar absorption ratio: 0.25; d) hemispherical emissivity: 0.85; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high-temperature and high-speed pneumatic scouring, the coating becomes brittle and yellow; g) thermal insulation performance: the thermal conductivity of the coating is 0.13 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.5% after being immersed in water for 24 hours; i) the coating adhesion is tested by the pull-belt method and there is powder loss.
[0127] The coating prepared in this comparative example has an off-white appearance, a uniform surface, no bubbles, and no cracks. However, due to the lack of a surface layer, the thermal radiation performance of the coating does not meet the requirements of low absorption and high emission. After 180 seconds of high-temperature, high-speed pneumatic scouring, the coating turns yellow significantly and has a tendency to become brittle and crack. After the bonding strength is tested using the tape pulling method, powdering occurs, and the subsequent thermal control requirements cannot be met.
[0128] Comparative Example 5
[0129] The difference between this example and Example 2 is that there is no bottom layer, and after preparation, a coating is obtained.
[0130] (1) Coating preparation: 20 g of hydroxyl-terminated methylphenyl silicone resin component A and 120 g of mixed solvent were added to a flask and mixed evenly for preliminary dispersion. 20 g of hydroxyl-terminated methylphenyl silicone resin component B was added for dispersion. After the resin and solvent were evenly dispersed, 133.6 g of zinc titanate powder, 72.05 g of mixed solvent and 167 g of glass beads were added. A high-speed dispersing device was used for sand milling dispersion at a speed of 1000 r / min for 2 h. The obtained paint was evenly dispersed without precipitation.
[0131] (2) Coating preparation: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0132] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 50-80 μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high temperature and high-speed pneumatic scouring, the heat-resistant material is carbonized and decomposed, and the coating cracks and falls off; g) thermal insulation performance: the thermal conductivity of the coating is 0.35 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.7% after being immersed in water for 24 hours; i) the adhesion of the coating is tested by the pull-belt method.
[0133] In this example, there is no bottom layer, so the coating has poor sealing properties for low-density heat-resistant materials and poor waterproof performance. In addition, since the surface layer has no heat insulation performance, when external heat is applied, the heat is directly transferred to the substrate, causing the substrate to decompose and release gas, resulting in cracks in the surface coating. At the same time, the bonding strength between the coating and the substrate is reduced, which cannot meet the subsequent on-orbit thermal control requirements of the coating.
[0134] Comparative Example 6
[0135] The difference between this example and Example 1 is that the thickness of the bottom layer exceeds the required range, and the surface layer cracks and peels off after the temperature resistance test of the bottom layer of the coating.
[0136] The steps of coating preparation include:
[0137] (1) Preparation of base coating: Add 20g of hydroxyl-terminated methylphenyl silicone resin component A and 100.2g of n-heptane to a flask and mix evenly for preliminary dispersion. Continue to add 20g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 44.54g of boron nitride powder, 22.26g of aluminum oxide whiskers, and 67g of glass beads. Use a high-speed dispersion device to sand grind and disperse at a speed of 1000r / min for 2h. The filtered paint A is evenly dispersed without precipitation. Add 35% of the volume of A hollow glass microspheres to a beaker, wet with the same volume of n-heptane to initially form a dispersion, mix with paint A, and use a stirrer to disperse and stir at a speed of 500r / min. After stirring for 2h, the base coating is obtained.
[0138] (2) Preparation of surface coating: Add 20 g of hydroxyl-terminated methylphenyl silicone resin component A and 120 g of mixed solvent into a flask and mix well for preliminary dispersion. Continue to add 20 g of hydroxyl-terminated methylphenyl silicone resin component B for dispersion. After the resin and solvent are evenly dispersed, add 80.16 g (80%) zinc titanate powder, 20.04 g alumina whiskers, 33.64 g mixed solvent, and 133.6 g glass beads. Use a high-speed dispersing device for sand milling dispersion at a speed of 1000 r / min for 2 hours. The resulting paint is evenly dispersed without precipitation.
[0139] (3) Coating preparation: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 7 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0140] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 820μm; c) solar absorption ratio: 0.19; d) hemispherical emissivity: 0.86; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196℃~150℃, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180s of high temperature and high-speed pneumatic scouring, the coating cracks and falls off; g) thermal insulation performance: the thermal conductivity of the coating is 0.09W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.3% after being immersed in water for 24h; i) the adhesion of the coating is tested by the pull-belt method.
[0141] In this case, because the bottom layer of the coating is too thick, the externally applied heat is conducted slowly and accumulates on the coating surface for too long, causing the coating surface temperature to exceed its own tolerance temperature. As a result, the coating decomposes, cracks and peels, and cannot meet subsequent use requirements.
[0142] Comparative Example 7
[0143] In this comparative example, a high-temperature resistant ceramic precursor resin was selected for resin selection. The resin will undergo a ceramicization reaction in a high-temperature environment and has good heat resistance, but poor toughness. It will crack on the surface of low-density heat-resistant materials and fail to meet the requirements of high-temperature and high-speed aerodynamic scouring tests. After cracking, it cannot meet the subsequent on-orbit thermal control requirements.
[0144] (1) Preparation of base coating: 40g of polysiloxazane ceramic precursor resin and 160g of butyl acetate were added to a flask and mixed evenly for preliminary dispersion. After the resin and solvent were evenly dispersed, 90g of boron nitride powder, 30g of aluminum oxide whiskers, and 120g of glass beads were added. The dispersion was performed by sand milling using a high-speed dispersion device at a speed of 1000r / min for 2h. The paint A obtained by filtration was evenly dispersed without precipitation. 35% of the volume of A hollow glass microbeads were added to a beaker, and the same volume of butyl acetate was used for wetting to initially form a dispersion liquid, which was mixed with paint A. The dispersion was stirred using a stirrer at a speed of 500r / min for 2h to obtain a base coating.
[0145] (2) Preparation of surface coating: 40 g of polysiloxazane ceramic precursor resin and 200 g of butyl acetate were added to a flask and mixed evenly for preliminary dispersion. After the resin and solvent were evenly dispersed, 128 g of zinc titanate powder, 32 g of alumina whiskers, and 160 g of glass beads were added. The mixture was dispersed by sand grinding using a high-speed dispersing device at a speed of 1000 r / min for 2 h. The obtained paint was evenly dispersed without precipitation.
[0146] (3) Preparation of coating: First, spray the primer on the surface of the low-density heat-resistant material, spray the primer 2 to 3 times, and spray the base layer after the surface is dry; spray the base layer 4 to 5 times, dry in the shade for 8 to 16 hours, and then cure at 50°C for 4 hours and then heat to 80°C for 20 hours; after the base layer is cured, spray the top layer 3 to 5 times, dry the coating in the shade at room temperature for 8 to 16 hours, and then cure at 80°C for 24 hours to obtain the coating.
[0147] The coating prepared in this example a) has a white appearance, a uniform surface, no blistering, no cracks, and no shedding; b) thickness: 400-550 μm; c) solar absorption ratio: 0.18; d) hemispherical emissivity: 0.87; e) thermal cycle performance: after 100 times of normal pressure thermal cycle test at -196°C to 150°C, the coating has a uniform appearance color, no obvious color difference, the coating does not fall off, and the thermal physical properties are stable; f) heat resistance: after 180 seconds of high temperature and high-speed pneumatic scouring, the coating cracks; g) thermal insulation performance: the thermal conductivity of the coating is 0.14 W / m·k at room temperature; h) waterproof performance: the water absorption rate of the coating is 0.4% after being immersed in water for 24 hours; i) the coating adhesion is slightly detached when tested by the pull-belt method.
[0148] In summary, the low-absorption and high-emission thermal control coating structure design of the present invention that is resistant to aerodynamic thermal environments can obtain a thermal control coating that has good low-absorption and high-emission thermal control performance and stability in complex aerodynamic thermal environments. At the same time, through the coating structure design and the use of fillers with specific types and proportions, a good multi-layer structure interlayer bonding force, low-absorption and high-emission thermal control performance, and an integrated coating that is heat-resistant, heat-insulating, and water-resistant can be obtained.
[0149] Further structural design analysis is as follows: adding hollow glass microsphere powder as filler in the bottom paint, due to the characteristics of hollow glass microspheres, can significantly improve the thermal insulation performance of the coating, ensuring that the heat-resistant substrate does not decompose at high temperatures. However, after the thermal insulation performance of the bottom layer is improved, the heat transmitted from the outside is prevented from being conducted downward. At the same time, since the composite coating is a low-absorption and high-emission thermal control coating, it has a certain thermal insulation ability. When the external heat enters the coating, it is difficult to dissipate outward through radiation heat dissipation, so it is easy to cause a large amount of heat accumulation. However, excessive accumulation of heat causes damage to the coating, making it impossible for the coating to pass the high-temperature, high-speed, and aerodynamic thermal ablation test and meet the on-orbit thermal control performance at the same time. Therefore, by adding fillers such as boron nitride and aluminum oxide whiskers, the heat resistance and thermal conductivity matching design of the coating is carried out, and the heat conduction between the surface layer and the bottom layer is adjusted to a balanced state. At the same time, by adding high-temperature resistant fillers such as boron nitride with relatively high specific heat capacity and high planar thermal conductivity in the bottom layer, the heat capacity and heat resistance of the coating are improved, the accumulated heat is dispersed, and the low-absorption and high-emission thermal control performance of the composite coating is guaranteed to be stable in a high-temperature environment.
[0150] Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims of the present invention.
Claims
1. A low-absorption and high-emission thermal control structure resistant to aerodynamic thermal environment, characterized in that: It includes a substrate and a coating; the coating is a bottom layer structure, with functional group-modified phenyl methyl silicone resin AB components as a binder, resin component A includes a base resin and a cross-linking catalyst, and resin component B includes a base resin and a cross-linking agent; the bottom layer structure includes a bottom layer and a surface layer; the bottom layer uses a mixed powder of boron nitride, aluminum oxide, and hollow glass microspheres as filler; the surface layer uses zinc titanate powder and aluminum oxide whiskers as filler.
2. The structure according to claim 1, characterized in that: The mass parts in the bottom layer meet the following requirements: 58-69 parts of resin A component, 100 parts of resin B component, 222.7-334 parts of boron nitride, and 111.3-167 parts of aluminum oxide; The mass proportions in the surface layer meet the following requirements: 58-69 parts of resin A component, 100 parts of resin B component, and 501-668 parts of total filler, wherein the proportion of zinc titanate powder to filler is greater than or equal to 80%, and the proportion of aluminum oxide whisker to filler is less than or equal to 20%.
3. The structure according to claim 1, characterized in that: The base resin of the resin A component and / or the resin B component includes at least one of a vinyl-terminated methylphenyl silicone resin, a hydroxyl-terminated methylphenyl silicone resin, and an alkoxy-terminated methylphenyl silicone resin.
4. The structure according to claim 1, characterized in that The structure satisfies at least one of the following: The boron nitride is hexagonal boron nitride in the form of flakes with a particle size of 10 to 50 microns, or the boron nitride is hexagonal boron nitride whiskers with a diameter of 0.5 to 1 micron and a length of 10 to 30 microns; The aluminum oxide is an aluminum oxide whisker with an aspect ratio of 10 to 20, a diameter of 0.5 to 1 micron, and a length of 10 microns; The cross-linking catalyst comprises at least one of the following: dibutyltin dilaurate, tetramethylammonium hydroxide, butyl titanate; The crosslinking agent includes at least one of the following: tetraethyl orthosilicate, diethylenetriamine, KH-CL silicon nitrogen crosslinking agent; The hollow glass microspheres have a particle size of 15 to 45 microns and a wall thickness of 2 microns; The thickness of the bottom layer is 300-600 μm, and the thickness of the surface layer is 50-100 μm; A first primer layer is provided between the substrate and the bottom layer, and a second primer layer is provided between the bottom layer and the surface layer. The first primer layer and the second primer layer are both obtained by spraying a primer, and the primer comprises a resin A component and a resin B component. The mass fractions of the primer satisfy 58 to 69 parts of the resin A component and 100 parts of the resin B component. The substrate includes one of a low-density thermal ablation resistant material, an aluminum alloy, a magnesium alloy, stainless steel, and a titanium alloy.
5. A method for preparing a low-absorption and high-emission thermal control coating resistant to aerodynamic thermal environment, characterized in that: The method is applied to a low-absorption and high-emission thermal control structure resistant to an aerodynamic thermal environment as claimed in any one of claims 1 to 4 to prepare a coating on a substrate, the method comprising: (1) Preparation of base coating: n-heptane solvent is added to resin component A, mixed and stirred to perform preliminary dispersion. After resin component A and solvent are evenly dispersed, resin component B is added and stirred continuously. After dispersion, filler powder is added and sand-milled with glass beads to evenly disperse the filler. After filtering, paint A is formed. n-heptane is added to hollow glass microspheres to evenly wet the hollow glass microspheres to form solution B, which is mixed and stirred with paint A to obtain an evenly dispersed base coating. (2) Preparation of surface coating: Add a mixed solvent of n-heptane and xylene to the resin component A, mix and stir to perform preliminary dispersion. After the resin component A and the solvent are evenly dispersed, add the resin component B, continue stirring, add zinc titanate powder, aluminum oxide whiskers and glass beads, and disperse by sand grinding to make the filler evenly dispersed; (3) Coating preparation: The coating is prepared by air spraying. First, spray the primer on the surface of the substrate. After the paint is evenly stirred, spray the paint. First, spray the base coat. After the base coat is cured, spray the primer and top coat, and then bake and cure.
6. The preparation method according to claim 5, characterized in that: Step (1) satisfies at least one of the following: Resin component A is a mixture of base resin, diluent and cross-linking catalyst, and the solid content of resin component A is 58-69%; The resin B component is a mixture of a base resin and a crosslinking agent, and the solid content of the resin B component is 100%; The amount of cross-linking catalyst added is 1 to 3% of the resin component A and the resin component B; The amount of crosslinking agent added is 4-6% of the resin component A and the resin component B; The diluent is at least one of the following: xylene, heptane, cyclohexane, n-hexane, butyl acetate; In paint A, the resin A component is 100 parts, the resin B component is 100 parts; the filler boron nitride is 222.7-334 parts, the filler aluminum oxide whisker powder is 111.3-167 parts, the solvent is 501-1002 parts, and the glass beads are 334-501 parts; In solution B, the amount of hollow glass microspheres added is 35-50% of the volume of paint A, and the amount of n-heptane added is 35-50% of the volume of paint A; The glass beads used in the sand grinding process of paint A have a size of 2 to 3 mm, the speed of the disperser during the sand grinding process is 1000 to 1300 r / min, and the dispersion time is 2 to 4 h; The solution B was stirred by a stirrer at a speed of 400 to 500 r / min for 2 to 3 hours.
7. The preparation method according to claim 5, characterized in that: Step (2) satisfies at least one of the following: The resin A component is 100 parts, the solid content of the resin A component is 58-69 parts, the resin B component is 100 parts; the total amount of filler consisting of a mixture of zinc titanate powder and aluminum oxide whisker is 501-668 parts, the proportion of zinc titanate powder to the filler is greater than or equal to 80%, the proportion of aluminum oxide whisker to the filler is less than or equal to 20%, the total amount after adding a mixed solvent of n-heptane and xylene is 668-960.25 parts, and the glass beads are 668-835 parts; The mass ratio of xylene:n-heptane is 1:1 to 1:2; The glass beads are 2 to 3 mm in size; During the sand grinding process, the speed of the disperser is 1000-1500 r / min, and the dispersion time is 2-4 hours.
8. The preparation method according to claim 5, characterized in that: Step (3) satisfies at least one of the following: The primer is a mixture of resin component A and resin component B, wherein the resin component A is 100 parts, the solid content of the resin component A is 58-69 parts, the resin component B is 100 parts, and n-heptane is 400-600 parts; The test piece substrate is any of the following: low-density thermal ablation resistant material, aluminum alloy, magnesium alloy, stainless steel, titanium alloy; The bottom layer spraying thickness is 300-600μm, and the curing method used is high temperature curing at 50-100℃ for 12-24h; The surface spray thickness is 50-100 μm, and the curing method used is high-temperature curing at 60-100°C for 24 hours.
9. The preparation method according to claim 8, characterized in that: The curing system for the bottom layer spraying is to cure at 50°C for 4 hours and then increase the temperature to 80°C for 20 hours.
10. The preparation method according to claim 8, characterized in that: The curing system for the surface spraying is 80℃ for 24h.
Citation Information
Patent Citations
Preparation method of n-zinc titanate powder and application
CN107827151A
Novel antistatic white thermal control coating and preparation method thereof
CN103666248A
Organic thermal control coating with low solar absorptivity and preparation method
CN113976410A
Anti-scouring radiation heat-proof coating for titanium alloy as well as preparation method and application of anti-scouring radiation heat-proof coating
CN114539922A
High-temperature reflective heat-insulation composite coating, preparation method thereof and application of high-temperature reflective heat-insulation composite coating in high-temperature-resistant motor
CN116285470A
Cited By
High-temperature-resistant anticorrosive paint for boiler and preparation method thereof
CN120310378A